2018
DOI: 10.1108/ihr-08-2018-0007
|View full text |Cite
|
Sign up to set email alerts
|

Translating emotional insights from hospitality employees’ comments

Abstract: Purpose The purpose of this paper is to use the data analysis method of sentiment analysis to improve the understanding of a large data set of employee comments from an annual employee job satisfaction survey of a US hospitality organization. Design/methodology/approach Sentiment analysis is used to examine the employee comments by identifying meaningful patterns, frequently used words and emotions. The statistical computing language, R, uses the sentiment analysis process to scan each employee survey commen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In the health care domain, prior use of this method has concentrated on patient opinions (Alemi & Jasper, 2014), social media (Cabling et al, 2017; Salas-Zárate et al, 2017), or policies (Ting et al, 2014). Sentiment analysis is being used by some employers as part of their employee satisfaction surveys and monitoring of internal communication channels, particularly technology companies that apply NLP to their product development (e.g., Twitter, IBM; Young & Gavade, 2018). Sentiment analysis opens the door to more robust and rapid data analysis that may help researchers quickly process a vast amount of qualitative information, for example, survey responses, bulletin boards, or electronic employee forums.…”
Section: Discussionmentioning
confidence: 99%
“…In the health care domain, prior use of this method has concentrated on patient opinions (Alemi & Jasper, 2014), social media (Cabling et al, 2017; Salas-Zárate et al, 2017), or policies (Ting et al, 2014). Sentiment analysis is being used by some employers as part of their employee satisfaction surveys and monitoring of internal communication channels, particularly technology companies that apply NLP to their product development (e.g., Twitter, IBM; Young & Gavade, 2018). Sentiment analysis opens the door to more robust and rapid data analysis that may help researchers quickly process a vast amount of qualitative information, for example, survey responses, bulletin boards, or electronic employee forums.…”
Section: Discussionmentioning
confidence: 99%
“…Phase 2content analysis of employee reviews Previous studies showed that employees' comments can help us understand their job satisfaction (Young & Gavade, 2018). This study used online employee reviews from Glassdoor.com to understand the differences in job satisfaction between housekeeping managers and employees.…”
Section: Ihrmentioning
confidence: 99%
“…Geetha et al (2017) applied lexicon-based sentiment analysis to study customer satisfaction in premium and economy hotels by analyzing customers’ online reviews. Young and Gavade (2018) showed that hotel management can use sentiment analysis to manage diversity issues. Prior studies commonly computed general sentiment polarity, which is a score indicating whether customers’ comments are positive or negative, to represent overall satisfaction (Geetha et al , 2017; Salehan and Kim, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%